Dampak kepemimpinan progresif kepala sekolah penggerak terhadap merdeka belajar di SD Muhammadiyah 1 dan SMA Muhammadiyah 1 Surakarta - Rusmanto Rusmanto; Sofyan Anief; Waston Waston (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
This research aims to investigate the impact of progressive leadership by school principals on independent learning at SD Muhammadiyah 1 and SMA Muhammadiyah 1 Surakarta. The research findings can be summarized as follows: The roles of the principals of SD Muhammadiyah 1 and SMA Muhammadiyah 1 Surakarta can be categorized as leaders who exhibit a progressive leadership style. Progressive leadership by the principals of SD Muhammadiyah 1 and SMA Muhammadiyah 1 Surakarta has a positive impact on students' abilities, including forward-thinking and innovative approaches, a focus on progressive and dynamic programs, involving various stakeholders (participatory) in their work and projects, utilizing advancements in IT for school programs (digital leadership), encouraging and mobilizing subordinates to take an active role, making decisions through consultation, consensus, and democracy, possessing the qualities of Asta Brata, and demonstrating a prophetic nature. The success factors of progressive leadership by the principals of SD Muhammadiyah 1 and SMA Muhammadiyah 1 Surakarta include government policies, funding, support from specific parties, and a favorable environment. On the other hand, the failure factors include the heterogeneity of human resources in both SD and SMA Muhammadiyah 1 Surakarta and inadequate facilities and infrastructure.